Malpractice in Nursing Case Reports - Şahin, Derya; Faikoğlu, Rehat; Şahin, İbrahim; Gökdoğan, Mira Rana; Yaşar, Sibel; Alparslan, Neşe; Dereli, Ebru; Faikoğlu, Gökhan (The Bulletin of Legal Medicine, 2014)
The issue malpractice, which is an important and multi-dimensional concept, has been debated in recent years and as a result, an increase of penalty and compensation cases are states that will be harmful to a patient by not giving treatment, by not applying standard medical applications with intent, fault, or negligence bythe health staff, and by wrong treatment applications. In malpractice cases may occur during nursing care, nurses are faced with penalty applications for being contrary to ethic principle is no damage his/her body integrity of ethical principles.In this study, cases of nursing malpractice were discussed with literature and it was aimed to draw attention errors and their reasons, importance of suitable approach for preventionKey Words: Malpractice, Nursing, Drug Applications.
Keywords: malpractice; nursing; drug applications